Pemetaan Potensi Energi Angin di Perairan Indonesia Berdasarkan Data Satelit QuikScat dan WindSat - Dida, Hero P; Suparman, Sudjito; Widhiyanuriyawan, Denny (Jurnal Rekayasa Mesin, 2016)
There were two kinds of monsoon winds in Indonesia. They are the east and the west monsoon winds. Both of them blow alternately in a year through the Indonesian territory. The velocity and energy of monsoon winds in Indonesian territorial sea were mapped by using MatLab program. The velocity and energy data were obtained by using QuikSCAT satellite from January 1999 until December 2009, meanwhile WindSat from January 2004 until December 2014. The results show that high energy of monsoon winds start from Indian oceans until Nusa Tenggara sea, then from Arafuru sea to Banda sea, Java sea, Karimata strait and the southern region of south Sulawesi.